Nurses' Experience in Caring for Palliative Patients - Prasetya, Candra Hadi; Sugiyanto, Emilia Puspitasari; Pramono, Wijanarko Heru; Aliyah, Zuhrotun (CV. Global Health Science Group, 2024)
Reducing suffering is an important thing in health services when healing is impossible. Palliative care is a chronic and terminal disease, which often happens when palliative patients have a poor prognosis. Objective: This study aims to describe the experiences of nurses in providing nursing care to palliative patients at Tugu Rejo Regional Hospital, Semarang. Method: This research uses a qualitative research approach on 6 nurse respondents with in-depth interview method Results: the results of this research found 3 themes of palliative care experiences, namely problems that arise during palliative patient care, including physical, psychological, social and spiritual problems. The second theme is the implementation of palliative care including management of signs and symptoms, psychological, social and spiritual support, communication, education, cross-sectoral collaboration. The third theme is barriers to care, including those that come from the patient, family, social environment, and knowledge about health services. Conclusions Increasing the ability of nurses is needed to improve the quality of palliative patient care services. This capability is expected to be able to overcome barriers to care and realize the goals of palliative care.